The effects of using multimodal texts on Grade 7 learners' intensive reading literature texts in EFAL classroom: a case of Kgakotlou Circuit, Capricorn-South District, Limpopo Province, South Africa - Machete, Tuwani (My University, 2024)
This study investigated the effects of using multimodal texts on Grade 7 English First Additional Language learners’ reading proficiency. A qualitative research approach was used, which involved a sample of ten Grade 7 EFAL learners, and four of their EFAL teachers to participate in this study. The data was collected using observations, document analysis and semi-structured interviews to determine the effects of using multimodal texts on learners’ reading proficiency during intensive reading lessons. For data analysis, inductive thematic analysis method was used. The findings of this study revealed that learners become bored when they only read traditional texts, but they find the use multimodal texts interesting. This study recommends that the Department of Basic Education should organize workshops on strategies to improve reading comprehension in EFAL using multimodal texts. The study recommends also that teachers should be encouraged to be innovative and not rely on teaching methods prescribed by the Department of Education only.
Thesis (M.Ed. (Language Education)) -- University of Limpopo, 2024
Keywords: Multimodal texts; Intensive reading; English First Additional Language; Multimodality in English language teaching; English language -- Study and teaching (Primary); English language -- Study and teaching; English literature; Reading -- Ability testing